2022
DOI: 10.3389/fpsyg.2022.901855
|View full text |Cite
|
Sign up to set email alerts
|

A Stage 1 Pilot Cohort Exploring the Use of EMDR Therapy as a Videoconference Psychotherapy During COVID-19 With Frontline Mental Health Workers: A Proof of Concept Study Utilising a Virtual Blind 2 Therapist Protocol

Abstract: ObjectiveThe COVID-19 pandemic has had a major impact on the delivery of psychological treatment. Due to social distancing requirements, the provision moved to videoconferencing psychotherapy (VCP). There is a paucity of empirical data supporting the efficacy of EMDR therapy as a VCP. This stage 1 pilot study tested an EMDR therapy scripted protocol, such as Virtual Blind 2 Therapist (VB2Tr), on frontline mental health workers as a VCP regarding fitness for purpose, distinctiveness, relevance, and efficiency.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 111 publications
1
4
0
Order By: Relevance
“…Future exploration of the impact that previous childhood and adult adverse experiences can have on the development of future traumatic stress symptoms from a workplace incident is warranted. This would align with current research that has examined this factor, particularly as it relates to mental health (see, e.g., Farrell et al, 2022;Perri et al, 2021).…”
Section: Future Researchsupporting
confidence: 77%
See 1 more Smart Citation
“…Future exploration of the impact that previous childhood and adult adverse experiences can have on the development of future traumatic stress symptoms from a workplace incident is warranted. This would align with current research that has examined this factor, particularly as it relates to mental health (see, e.g., Farrell et al, 2022;Perri et al, 2021).…”
Section: Future Researchsupporting
confidence: 77%
“…Similarly, a comparison of seven sessions of CBT and R-TEP for ASD delivered via Skype found both interventions were effective in reducing anxiety, trauma, and depressive symptoms (Perri et al, 2021). A recent proof-of-concept study also found evidence that EMDR can be delivered via videoconference, however, concluded a clinical trial was warranted (Farrell et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study investigated the efficacy of EMDR therapy as a videoconferencing psychotherapy in 24 frontline mental health workers, exploring the treatment effect on the core characteristics of the trauma memory, namely, subjective disturbance, belief systems, memory intensity, vividness, and levels of emotionality. These results suggested the potential clinical benefits of using the EMDR as a videoconference psychotherapy (Farrell et al, 2022 ).…”
Section: Efficacy Of Emdr Interventions On the Long-term Psychologica...mentioning
confidence: 85%
“…In the current project, the standard EMDR protocol was utilized within a relatively brief timeframe (4 to 8 sessions), with sessions exclusively conducted by an EMDR Consultant remotely via Zoom. This has been shown to be as effective as face-to-face treatment ( 20 , 21 ). It was also practically advantageous because the PCN covers a large and rural geographical area which means that the therapist did not need to travel between six practices every week and could offer the travel time as sessions to other patients and the patients could also benefit from not needing to commute.…”
Section: Methodsmentioning
confidence: 99%